Improvement of normative provisions for heat pumps as a mechanism for the implementation of European directives - Sokolovska I.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2018)
We consider the currently in force European Directives 2009/28/EC, 2009/125/EC, 2010/30/EC, and 2010/31/EU, Regulations and other normative documents corresponding to them as well as international standards for heat pumps, the presence of which confirms large-scale practical application of heat pumps in the world. We show the degree of their introduction in Ukraine. We also determine the necessity of active introduction of the national standards for heat pumps harmonized with the international ones in Ukraine. It will favor the implementation of mentioned European Directives and corresponding Regulations.